(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article examines the key elements that determine the profitability of enterprises and identifies the main factors influencing the formation and change in the level of profit. The influence of the internal and external environment of organizations is analyzed, and recommendations are provided to improve business efficiency. Based on the analysis of practical data on the banking sector of the Republic of Uzbekistan for 2023, the dominant role of interest income is established and its impact on the profitability of financial institutions is considered. The results of the economic analysis of the joint-stock company are also presented, trends in changes in gross, net and retained earnings for the period 2020-2023 are identified. Negative dynamics of the main financial indicators of the enterprise are noted, indicating the need to take urgent measures to optimize costs and improve production and commercial policies to stabilize the financial condition and increase the competitiveness of companies.